2015
DOI: 10.1096/fj.14-259085
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin directly stimulates osteoclast precursors and induces bone loss

Abstract: Erythropoietin (EPO) primarily regulates red blood cell formation, and EPO serum levels are increased on hypoxic stress (e.g., anemia and altitude). In addition to anemia, recent discoveries suggest new therapeutic indications for EPO, unrelated to erythropoiesis. We investigated the skeletal role of EPO using several models of overexpression (Tg6 mice) and EPO administration (intermittent/continuous, high/low doses) in adult C57Bl6 female mice. Using microcomputed tomography, histology, and serum markers, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
192
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(209 citation statements)
references
References 60 publications
16
192
1
Order By: Relevance
“…Impaired osteogenesis was recently described in the tg6 mouse by other investigators and was likewise reported in animal models of thalassemia [31, 4042]. In this disorder, a defective hemoglobin molecule leads to continuous erythroid destruction and anemia, which then causes a rise in circulating EPO and a subsequent expansion of defective erythroids, in a vicious circle of “ineffective erythropoiesis”.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Impaired osteogenesis was recently described in the tg6 mouse by other investigators and was likewise reported in animal models of thalassemia [31, 4042]. In this disorder, a defective hemoglobin molecule leads to continuous erythroid destruction and anemia, which then causes a rise in circulating EPO and a subsequent expansion of defective erythroids, in a vicious circle of “ineffective erythropoiesis”.…”
Section: Discussionmentioning
confidence: 81%
“…However the results on the skeleton are controversial. One group of investigators showed a positive effect on bone mass and bone formation in newborn and older animals treated with EPO [12] while two other groups observed that exogenous EPO administration resulted in bone loss caused by increased bone turnover [30, 31]. The debate extends on the potential mechanisms of EPO action in vivo and whether EPO has direct humoral effects on bone homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary bone marrow-derived macrophages (BMDMs) were isolated from the femora and tibiae of adult C57BL/6J-RCC mice, as previously described21. Briefly, cells were cultured overnight in 6-well dishes at 37 °C in a humidified atmosphere with 5% CO 2 in alpha modified Eagle’s medium (αMEM, Life Science Technology, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the osteoclastogenesis assay, BMDM, which are the same as preosteoclasts in vitro , were plated in 96-well plates (7,000 cells per well) in standard medium supplemented with 20 ng/ml M-CSF and 50 ng/ml RANKL (R&D Systems, Minneapolis, MN, USA), replaced every 2 days, as previously described21. Treatments (either LPS or titanium particles) were added after two days of incubation.…”
Section: Methodsmentioning
confidence: 99%